Analisis Tantangan dan Peluang Implementasi E-Governance di Pemerintah Kota Samarinda - Dyah Rahayuning Perwitasari; Bambang Irawan (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Sragen, 2026)
This study aims to analyze the challenges and opportunities in the implementation of e-governance in the Samarinda City Government, focusing on the role of technology and infrastructure in supporting the digital transformation of public services. Digital transformation in the government sector is expected to enhance efficiency, transparency, and the quality of services to the public. However, the implementation of e-government systems often faces various obstacles affect their success. This research methodology employs a literature review approach to analyze the existing challenges, as well as the opportunities that can be leveraged in the e-government implementation process. The literature review references various previous studies related to technology infrastructure, digital literacy, and experiences with e-government implementation in other cities across Indonesia. The findings of the study indicate that the main challenges faced by the Samarinda City Government include limitations in digital infrastructure, such as uneven internet access, inadequate hardware, and low digital literacy among government officials and the public. Additionally, resistance to change from government employees also serves as an inhibiting factor. The study also identifies significant opportunities in e-government implementation, such as enhanced transparency in budget management, improved public participation, and the simplification of administrative processes that could accelerate public services. The conclusion of this study is to expedite digital transformation in the Samarinda City Government, there is a need for increased infrastructure readiness, digital literacy training for government employees, and a more inclusive approach to involving the public in technology use. By capitalizing on these opportunities, the Samarinda City Government can overcome existing challenges and create a more transparent, efficient, and responsive government system that meets the needs of the public.